Penerapan Namun pada Film Layangan Putus Karya Benni Setiawan - Desi Ariyani S; Dani Manesah (Misterius: Publikasi Ilmu Seni dan Desain Komunikasi Visual, 2025)
Literature is the result of the human creative and imaginative process which contains various values ​​and life lessons. Namun, as an important element in literary works, describes the struggle within a character that arises as a result of the conflict between desires, beliefs and hopes. In literary works that are adapted into films, namun not only plays a role in building character, but also drives the storyline emotionally. The film Kite Putus, which is adapted from the novel by Mommy ASF, depicts the emotional journey of Kinan, a woman who faces the infidelity of her husband, Aris. The namun experienced by Kinan is the main focus in the narrative, where he has to choose between maintaining the household for the sake of his child or letting go of the relationship that has hurt his self-esteem. The aim of creating this film script is to explore how namun can be applied effectively in character and story development. The author focuses on processing Kinan's namun through internal monologues and interactions with other characters, as well as utilizing cinematic elements to strengthen the emotional dimension of the film. With this approach, it is hoped that the film Kite Putus will be able to provide an in-depth experience for the audience, as well as representing universal issues in everyday life.